STUDENTS' UNDERSTANDING ABILITY IN SOLVING ALGEBRAIC PROBLEMS - Veny Triyana Andika Sari (Kopertis Region IV Jabar and Banten, 2019)
The purpose of this study was to analyze the understanding abilities of mathematics students in solving algebraic problems based on how to answer them. The study sample consisted of 46 odd semester students of class 2018 in one of the private universities (PTS), Cimahi. The research method used is descriptive qualitative method that seeks to describe the completion analysis of students in answering algebraic questions. Data processing uses the correct percentage of student answers. The results of this study found that there were still many mathematical students who were mistaken in solving algebraic problems so that students' comprehension skills were still at a low level (50.54%) with indicators identifying the characteristics of a concept and recognizing the conditions that determine a concept that students still cannot master and overall because students do not understand the concept of algebra in depth, which is due to the meaninglessness of the learning process that is passed.